ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN TERNAK SAPI BERBASIS SUMBERDAYA PAKAN DI KABUPATEN MANDAILING NATAL, SUMATERA UTARA - ., MARIMPUN (Fakultas Peternakan Universitas Udayana, 2023)
This research aims to analyze the potential and strategy for developing livestock based on feed resources in Man- dailing Natal Regency, North Sumatra. The method used in this research is the SWOT analysis survey method. The results of the research show that the potential feed resources in Mandailing Natal Regency, North Sumatra come from intercrop forage (orange, oil palm) forage in galengan rice fields, agricultural crop waste and agricultural/ agricultural processing waste with a total feed production of 41,028,554 Kg Dry Ingridients/year and can accommo- date 14,987 Livestock Unit. The cattle development strategy based on SWOT analysis is to build a cattle feed proces- sing industry by utilizing feed resources, industrial raw materials, geographical location and government support.